Analysis of Post-Pandemic Quantitative Easing Policy and Its Impact on the Global Economy - Syafii, Akhmad; Atmoko, Dwi (Asosiasi Persatuan Pengusaha Muda Teknik Informatika, 2025)
Quantitative easing (QE) policy has been central banks' main strategy to deal with the economic impact of the COVID-19 pandemic. This study aims to analyze the impact of post-pandemic QE on inflation, financial stability, and global economic growth. The method used was secondary data analysis from central bank reports, international financial institutions, and academic publications, with a research period between 2018 and 2023. The results showed that QE policies contributed significantly to the increase in inflation, with a positive correlation between the amount of assets purchased by the central bank and the inflation rate. In addition, QE also plays a role in stimulating economic growth, albeit on a more moderate scale. This research contributes for policymakers to formulate appropriate monetary strategies to maintain global economic stability without triggering a surge in inflation.